The Use of AI Media in Indonesian Language Learning at SMPN 3 Taman (Case Study, Learning Material Short Story Making Narration) - Satunggale Kurniawan; Rahman, Muhammad Afifi; Yuventius Sugiarno (Yayasan Insan Mulia Bima, 2025)
Along with the development of technology, the use of information and communication technology (ICT) in the world of education is increasingly inevitable. One form of ICT utilization that is currently developing rapidly is the use of artificial intelligence (AI) in the learning process. AI technology has great potential in supporting the teaching and learning process, both in terms of delivering materials, interacting with students, and in terms of assessment and evaluation. In junior high schools, especially at SMPN 3 Taman, learning Indonesian still faces challenges in developing students' writing skills, especially in narrative learning materials, such as making short stories. Learning short stories requires creativity, understanding of text structure, and good language skills. However, this learning process is often hampered by limited teaching resources and less innovative teaching techniques. This study analyzes the effectiveness of using AI media in learning to write short stories at Taman 3 State Junior High School, Sidoarjo Regency. This study uses a qualitative approach with a case study method in several secondary schools that have implemented AI in Indonesian language learning, By using a case study method involving observation, interviews, and document analysis, the results of the study show that AI contributes to increasing student creativity, helping to compile a more systematic storyline, and increasing student confidence in writing. However, the use of AI in learning to write short stories still requires teacher guidance so that it remains in line with educational goals and does not reduce students' natural creativity.